2017
DOI: 10.1007/978-3-319-70281-0_6
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Curriculum in UK University Sustainability Reports

Abstract: One of the major barriers to incorporating sustainability in the HE curriculum is its absence from the university's sustainability strategy, the annual reflection of which is the institution's sustainability report. While strategies stipulate future targets, reports record what has already been achieved in the previous academic year. In that respect, sustainability reports function as internally created reviews of an institution's sustainability activity. Various reviews of sustainability curriculum have taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The tools outlined above emphasize sustainability integration across four key functions, namely; education, research, community and operations. Therefore, universities that publish sustainability reports, typically include their sustainability curriculum as a central component (Kosta, 2018). For example, CSAF assesses curricular offerings based on the proportion of modules with some sustainability content and the number of students taking those modules.…”
Section: Sustainability Reporting In Higher Educationmentioning
confidence: 99%
“…The tools outlined above emphasize sustainability integration across four key functions, namely; education, research, community and operations. Therefore, universities that publish sustainability reports, typically include their sustainability curriculum as a central component (Kosta, 2018). For example, CSAF assesses curricular offerings based on the proportion of modules with some sustainability content and the number of students taking those modules.…”
Section: Sustainability Reporting In Higher Educationmentioning
confidence: 99%
“…Rodríguez Bolívar et al (2013) investigated the online reporting of corporate social responsibility in 25 Anglo-American universities and concluded that universities pay little attention to the online disclosure of sustainability activities. Furthermore, there are some case studies (Dagilienė and Mykolaitienė, 2016;An et al, 2017;Kräusche and Pilz, 2018;Schoeps and Hemmer, 2018) and more comprehensive content analyses that analyse sustainability reports by using small international samples (Lozano, 2011;Romolini et al, 2015;Bice and Coates, 2016) or comparing more or less small samples of different countries such as Australia (Gamage and Sciulli, 2016; Schaffhauser-Linzatti and Ossmann, 2018), Austria (Lopatta and Jaeschke, 2014;Schaffhauser-Linzatti and Ossmann, 2018), Canada (Fonseca et al, 2011;Sassen and Azizi, 2018b), Germany (Lopatta and Jaeschke, 2014;Sassen et al, 2014), Italy (Siboni et al, 2013;Del Sordo et al, 2016), the UK (Kosta, 2018) and the USA (Sassen and Azizi, 2018a). All the investigations came to the unanimous conclusion that sustainability reporting at higher education institutions is still in its early stages, and the levels of disclosure of sustainability information are still rather low.…”
Section: Previous Research On Sustainability Reporting Of Higher Education Institutionsmentioning
confidence: 99%
“…All the investigations came to the unanimous conclusion that sustainability reporting at higher education institutions is still in its early stages, and the levels of disclosure of sustainability information are still rather low. The UK study by Kosta (2018) has a specific focus and investigates the sustainability curriculum in UK university sustainability reports. Kosta (2018) found that 4 per cent of the UK higher education institutions report on their sustainability curriculum in a comprehensive manner.…”
Section: Previous Research On Sustainability Reporting Of Higher Education Institutionsmentioning
confidence: 99%
See 2 more Smart Citations